(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Eighteenth century France was predominantly agrarian in structure in spite of the fact that this was an age of economic and intellectual progress. An age in which through development of capitalist enterprise, industry, trade and commerce, the bourgeoise became economically as well as politically important. All the economic development took place in the background of old regime, decadent feudal system, order of Estates, impoverished peasant class, backward agrarian system. The article aims to look at the economic development before and after the French revolution of 1789 especially at the impediments in the way of Capitalist development.